Inhibition of quorum sensing, biofilm and motility of Escherichia coli by Staphylococcus warneri MG1_8 bioactive compounds - Chaichana, Nattarika; Sukpondma, Yaowapa; Sermwittayawong, Decha; Sermwittayawong, Natthawan (Penerbit Universiti Kebangsaan Malaysia, 2024)
Quorum sensing (QS) system in bacteria, mediated by a small signaling molecule called an autoinducer (AI), promotes biofilm formation and other virulence factors that contribute to reducing the susceptibility of treatment agents. Escherichia coli is considered bacteria contaminated in the food industry with their biofilm-forming ability which allows them to adhere on surfaces. In this study, the cell-free supernatant (CFS) extract of mangrove forest isolated bacteria, Staphylococcus warneri MG1_8, was purified and its possible quorum sensing inhibitor (QSI) metabolites were identified. Fraction A was separated from S. warneri MG1_8-CFS extract using gel column chromatography and confirmed as a positive fraction by its ability to inhibit bioluminescence in the biosensor strain Vibrio campbellii ATCC BAA-1119, showing 76% inhibition. In addition, pyridoxine (PN) was identified as a major compound in the S. warneri MG1_8 CFS extract. The minimum inhibitory concentration (MIC) of PN against E. coli ATCC 25922 was 50 mg/mL. The PN at 1/4MIC reduced biofilm formation and cell adherence in E. coli strains, as observed under scanning electron microscopy (SEM). Moreover, motility and AI-2 signaling also decreased after exposure to PN at sub-MIC levels. Current research demonstrates that PN can inhibit biofilm formation and motility by interfering with AI-2 QS, suggesting it could be considered a novel biocontrol agent to reduce bacterial contamination in food production.